Development of Co-lean (Sm, Y)(Fe, Co, Ti)12 compounds with large saturation magnetization. (1st April 2022) - Tozman, Pelin; Sepehri-Amin, Hossein; Tang, Xin; Ohkubo, Tadakatsu; Hono, Kazuhiro
Abstract: Large saturation magnetization in the SmFe12 -based compounds is realized by substitution of scarce Co for Fe site. However, reduction of Co is necessary for their potential practical applications. In this work, we successfully decrease the concentration of Co, from 17.3 at% to 8.7 at% while maintaining large μ 0 M s of 1.41 T at 300 K in Ti reduced Sm0.8 Y0.2 (Fe0.9 Co0.1 )11.25 Ti0.75 compound. In addition, we report the highest μ 0 M s for bulk Sm0.8 Y0.2 (Fe0.8 Co0.2 )11.25 Ti0.75 with μ 0 M s = 1.49 T, μ 0 H a = 9.14 T at 300 K and T c = 831 K. We demonstrate (Sm0.8 Y0.2 )Fe12 -based compounds exhibit superior intrinsic magnetic properties than Nd2 Fe14 B above 473 K.